Fund flows inducing mispricing of risk in competitive financial markets - Axel Stahmer (European School of Management and Technology (ESMT), 2015)
This paper studies the effect of new fund flows on investment behavior and the resulting equilibrium price of risk. The Small Fund Industry model shows equilibria with overinvestment in unprofitable and underinvestment in profitable investment opportunities. The Large Fund Industry model derives market prices for risk and analyzes the resulting price distortions in equilibrium. New flow of funds to the asset management industry lead to inefficient investment decisions, mispricing of risk, and distortion of market implied probabilities. Furthermore, the paper provides an explanation for partial market failure and trade among identical asset managers without assuming heterogeneous beliefs.
urn:nbn:de:101:1-201511278117
Keywords: D53; D80; G01; G02; G11; G12; G20; 650; asset pricing; mutual funds; flow of funds; mispricing; misallocation of capital; overinvestment; underinvestment; investment decision; implied probabilites